The role of bilingual education in promoting cultural diversity among school students in the Interior of Palestine from the Teachers’ Perspective - Abbas, Shireen Saed (Journal of Educational and Psychological Sciences, 2025)
The primary aim of this study was to examine the role of bilingual education in promoting cultural diversity among school students in the Interior of Palestine from the perspective of teachers. An analytical descriptive approach was adopted, and a questionnaire was used to collect data from the entire population of teachers at Al-Jalil School in northern Palestine, one of the “Hand in Hand” schools implementing a bilingual education system (Arabic and Hebrew), totaling 32 participants. The findings revealed a moderate role of bilingual education in enhancing cultural diversity among students, as perceived by the study participants. This, in turn, positively contributes to fostering mutual understanding, harmony, and respect among students, creating a healthy and supportive environment that enhances cognitive performance and academic achievement while strengthening cultural diversity that benefits society as a whole. Based on these findings, the study recommended increasing the focus of schools in the Interior of Palestine on implementing bilingual education systems, establishing mechanisms to monitor and evaluate their application, and introducing curricula, activities, or programs within these schools aimed at familiarizing students with different cultures to enrich their cultural awareness.